2015
DOI: 10.1111/1346-8138.12859
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical systemic and vascular inflammation detected by 18F‐fluorodeoxyglucose positron emission tomography/computed tomography in patients with mild psoriasis

Abstract: Severe psoriasis is a systemic inflammatory disease involving major arteries and internal organs. The association between psoriasis and arterial inflammation, however, has been noted mostly in patients with moderate to severe psoriasis. Therefore, it is still not clear whether mild psoriasis also increases the arterial inflammation and cardiovascular disease. In this study, we aimed to investigate systemic inflammation using 18 F-fluorodeoxyglucose positron emission tomography/computed tomography (FDG-PET/CT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…All of these conditions increase the risk for the development of type 2 diabetes and cardiovascular disease (67-69) (Figure). Consistent with this hypothesis, subclinical systemic and vascular inflammation have been detected by 18 F-fluorodeoxyglucose positron emission tomography/computed tomography in patients with psoriasis (70). In a six-month prospective study, carotid arterial stiffness in patients with psoriasis was significantly improved by anti-TNF-α therapy (71).…”
Section: Pathophysiology Of Comorbiditymentioning
confidence: 69%
“…All of these conditions increase the risk for the development of type 2 diabetes and cardiovascular disease (67-69) (Figure). Consistent with this hypothesis, subclinical systemic and vascular inflammation have been detected by 18 F-fluorodeoxyglucose positron emission tomography/computed tomography in patients with psoriasis (70). In a six-month prospective study, carotid arterial stiffness in patients with psoriasis was significantly improved by anti-TNF-α therapy (71).…”
Section: Pathophysiology Of Comorbiditymentioning
confidence: 69%
“…Observations from 18 F‐fluorodeoxyglucose positron emission tomography/computed tomography (FDG PET/CT) studies also validate the hypothesis that psoriasis is a systemic inflammatory disease. In these studies, patients with moderate‐to‐severe psoriasis demonstrate subclinical inflammation in the liver, joints and tendons, in addition to significantly increased global arterial and subcutaneous inflammation, and patients with mild psoriasis had subclinical inflammation in the aorta . Also, ultrasound of femoral arteries can improve detection of subclinical atherosclerosis in patients with moderate‐to‐severe psoriasis and insulin resistance helps to provide a better prediction of subclinical atherosclerosis than traditional CVD risk factors .…”
Section: Psoriasis: a Systemic Inflammatory Diseasementioning
confidence: 99%
“…Different authors observed higher common carotid artery intima‐media thickness (IMT) in patients with severe psoriasis compared with control subjects, while others measured various cardiovascular biomarkers . Interestingly, even in patients with mild psoriasis subclinical systemic and vascular inflammation detected by 18 F‐fluorodeoxyglucose positron emission tomography (FDG‐PET)/computed tomography (CT) has been described . Systemic therapy for psoriasis, for example, methotrexate or tumor necrosis factor‐α inhibitors (anti‐TNF‐α), seems to be an effective approach to decrease cardiovascular events in psoriasis patients .…”
Section: Introductionmentioning
confidence: 99%